Relationship between Waste Cover Area with Physical and Chemical Characteristics of Mangrove Ecosystem in Pulau Dua Nature Reserve, Serang, Banten - Pratama, Farros Hilmi; Suwandhi, Ichsan; Lastini, Tien (3BIO: Journal of Biological Science, Technology and Management, 2025)
Pulau Dua Nature Reserve has undergone significant changes to its land, affecting its physical and chemical properties. Additionally, the increasing problem of scattered plastic waste raises concerns about its negative impact on the ecosystem. This study aims to analyze the physical and chemical characteristics of Pulau Dua Nature Reserve and examine the relationship between the proportion of plastic waste cover area and environmental parameters. Microclimate, soil, and plastic waste proportion area data, especially plastic, were collected at 34 points using systematic random sampling, while water salinity was measured using accidental sampling because the pools for measuring salinity were not spread throughout the research area. A comparative analysis based on literature review and previous studies with mangrove ecosystems indicates that Pulau Dua’s mangrove vegetation is under threat from various environmental factors. Among these, the proportion of plastic waste cover area has the strongest correlation as moderate positive correlation with bulk density in Pearson Correlation Matrix. Independent Sample T-test comparing plastic waste cover area proportion based on bulk density class confirms that class 4 significantly affects bulk density. In conclusion, several physical and chemical parameters in Pulau Dua Nature Reserve do not align with optimal conditions for mangrove vegetation. The most related factors to plastic waste cover area proportion are bulk density because the indication is that areas covered with plastic waste are areas that are frequently passed by humans, thus increasing the bulk density of the soil. Value of bulk density will significantly different when proportion of plastic waste cover more than 2.5% based on Independent Sample T-test.